DIAGNOSTIC CAPABILITIES OF ULTRASOUND EXAMINATION OF THE KNEE JOINT AT THE CURRENT STAGE (LITERATURE REVIEW) - Baburkina, Olena; Ovchynnikov, Oleg; Bludova, Maryna (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Ultrasound examination (ultrasound) of the knee joint left is one of the main methods of diagnosing its diseases and injuries, which are constantly improved thanks to the use of more accurate diagnostic equipment. Objection. Analyze modern scientific and practical information regarding the possibilities of ultrasound examination of the knee joint and determine pathological changes in its tissues, for the diagnosis of which this technique can be used. Methods. Selected and analyzed scientific articles for the last 6 years, in which the use of knee joint ultrasound is given from the Google search engine, scientific metrics databases PubMed, Medline and other relevant sources scientific and medical information. Results. Analyzed modern literature on the use of knee joint ultrasound in medical practice. Defined orthopedic pathological diseases and areas of the knee joint which investigated by ultrasound. This technique is used for diagnosis of gonarthrosis, synovitis, assessment blood circulation and fluid in the knee joint, Backer’s cyst, neoplasms, pathology of menisci, injuries and inflammations ligaments, tendons and muscles. Most doctors and patients prefer the ultrasound technique due to its mobility, without heartburn, almost complete absence of contraindications to carrying out. Today, this research is necessary and an effective method of diagnosing orthopedic pathology traumatic diseases, including knee joint, both individually and in combination with other methods (radiography, computer tomography, magnetic resonance tomography, etc.). It should be noted that the method ultrasound becomes indispensable in case of contraindications to the procedure magnetic resonance imaging. Conclusions. Ultrasound of the patient of diseases and injuries of the knee joint is modern and effective by the method of express diagnostics and can be used both independently and in combination with other methods of diagnostics of pathological changes in the tissues of this localization.